2017
DOI: 10.3892/mmr.2017.7359
|View full text |Cite
|
Sign up to set email alerts
|

Mdivi-1 attenuates sodium azide-induced apoptosis in H9c2 cardiac muscle cells

Abstract: The aim of the current study was to investigate the effect of mitochondrial division inhibitor 1 (Mdivi-1) in sodium azide-induced cell death in H9c2 cardiac muscle cells. Mdivi-1 is a key inhibitor of the mitochondrial division protein dynamin-related protein 1 (Drp1). Mdivi-1 was added to H9c2 cells for 3 h, after which, the cells were treated with sodium azide for 24 h. Cell viability was measured by Cell Counting kit-8 assay. DAPI staining was used to observe nuclear morphology changes by microscopy. To fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Excessive mitochondrial fission causes the uneven distribution of mitochondrial DNA into daughter mitochondria, leading to the inability of mitochondria to produce sufficient ATP (Gorick, Sheybani, Curley, & Price, ; Ju et al, ). In our study, we found that ox‐LDL‐induced oxidative stress altered the mitochondrial membrane, reducing mitochondrial potential and opening the mPTP (Gao et al, ; X. Xu et al, ). This mitochondrial functional and structural damage was accompanied by mitochondrial apoptosis in endothelial cells.…”
Section: Discussionmentioning
confidence: 70%
“…Excessive mitochondrial fission causes the uneven distribution of mitochondrial DNA into daughter mitochondria, leading to the inability of mitochondria to produce sufficient ATP (Gorick, Sheybani, Curley, & Price, ; Ju et al, ). In our study, we found that ox‐LDL‐induced oxidative stress altered the mitochondrial membrane, reducing mitochondrial potential and opening the mPTP (Gao et al, ; X. Xu et al, ). This mitochondrial functional and structural damage was accompanied by mitochondrial apoptosis in endothelial cells.…”
Section: Discussionmentioning
confidence: 70%
“…The current work also revealed that AlCl 3 (50 mg/kg/day) significantly elevated the serum levels of cholesterol, TGs, and LDL with a reduced serum level of HDL (Figure ), while at a high dose, NaN 3 (17 mg/kg/day) caused mortality. Investigations have shown that NaN 3 can cause sudden lowering of blood pressure, tachycardia, cardiac arrhythmia, and cardiac toxicity; moreover, late onset of hypotension presents an ominous sign of death . Any of these effects reported earlier could be a cause of sudden death in the experimental animals of the current study exposed to NaN 3 (17 mg/kg/day).…”
Section: Discussionmentioning
confidence: 99%
“…Investigation has found that aluminum toxicities may include fibrosis, myocarditis, thrombosis, ischemic stroke, AD, dementia, pancreatitis, pancreatic necrosis, and DM . Numerous reports have revealed that NaN 3 poisoning causes severe hypoxemia, myocardial fibrosis, and extensive damage in the nervous and cardiac systems . In this study, fibrosis of the brain, heart, and pancreatic tissue, after exposure to different doses of AlCl 3 and NaN 3 , was analyzed via Masson’s trichrome staining (Figures , , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some pathological conditions, such as acute kidney injury and diabetic nephropathy [ 11 , 12 ], excessive mitochondrial fission results in increased mitochondrial fragmentation which inhibits the cellular respiratory chain, leading to cellular dysfunction and aggravating tissue damage [ 13 , 14 ]. Mitochondrial fission is primarily mediated by dynamin-related protein 1 (Drp-1) [ 15 ], a member of the dynamin family of large GTPases, mostly localized in the cytoplasm [ 16 ]. Drp-1 is recruited to the outer membrane of mitochondria by a variety of adaptor proteins and then aggregates along the site of mitochondrial fission in the future [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%